Reorganizing the layout as a production optimization strategy - Gilson Pires da Rosa; Tânia Craco; Zaida Cristiane dos Reis; Cristine Hermann Nodari (GEPROS: Gestão da Produção, Operações e Sistemas, 2014)
Organizations are embedded in competitive environments that require the improvement of manufacturing practices, highlighting the physical arrangement as a major challenge in industrial management. This paper aims to demonstrate the importance of layout as a way to increase the competitiveness of organizations. The theoretical concepts of consolidation began with layout, the different existing models and processes required for implementation and adaptation. Thus, we established an understanding of organizational production flow and sensitivity required for reflections on process improvement in a hydraulic cylinder manufacturing industry. The methodology used was an exploratory and descriptive study conducted through a case study. Therefore, the research was conducted using primary data with semi-structured interviews, and secondary data collected from documents and organizational reports. The results of the study indicated opportunities for improvement in the production flow, allowing for greater capacity and increased profits for the organization anticipating the return on capital invested in the business.